Interaction between the TCF7L2 gene and dietary intake on metabolic syndrome risk factors among Saudi Arabian adults - Al-odinan, Maha S.; Aljefree, Najlaa M.; Almoraie, Noha M.; Bakarman, Marwan A.; Alhadrami, Hani A.; Shatwan, Israa M. (Frontiers in Nutrition, 2025)
IntroductionTranscription factor-7-like 2 (TCF7L2) is the most critical type 2 diabetes (T2D) gene identified to date. The single-nucleotide polymorphism (SNP) rs7903146 in TCF7L2 in T2D interacts with dietary factors; however, research on nutrigenetics among Saudi Arabians is limited. This study investigated the interaction between the SNP rs7903146 and dietary intake on factors that may contribute to MetS among Saudi Arabian adults.MethodsThis cross-sectional study included 271 adult participants (aged 20–55 years) of both genders with or without overweight or obesity (body mass index between 18–35 kg/m2). Anthropometric measurements and dietary assessments using a food frequency questionnaire were performed. Fasting blood samples were collected to analyze serum lipid, glucose, and insulin levels. Genetic analysis was performed using real-time polymerase chain reaction. Univariate regression was used to examine the association between the TCF7L2 SNP rs7903146 and laboratory parameters, and to test SNP-diet interactions. The additive model was used in the analysis and the T allele was the effect allele.ResultsA marginal significant association was observed between SNP rs7903146 and waist circumference (WC) (p = 0.05). Carriers of TT genotype had the highest WC (83.5 ± 20.1 cm), when compared with the CC genotype (80 ± 14.2 cm) and the TC genotype (77.9 ± 13.9 cm). The SNP rs7903146 was significantly associated with total energy intake (p = 0.04) and saturated fatty acids (SFA, p = 0.005), and TT carriers had the highest total energy and SFA consumption (3606.9 ± 1554.7 kcal, 66.8 ± 52.0 g, respectively). Only one near significant interaction was observed between SNP rs7903146 and total energy intake on insulin levels (p = 0.04), with carriers of the TT genotype showed a greater reduction in insulin values (−5.3 ± 3.5) at lower energy intake when compared with the CC (−2.4 ± 3.1), and TC (−4.7 ± 2.8). No significant interaction was found.ConclusionThe present study observed significant associations between SNP rs7903146 and total energy and SFA consumptions. The TT carriers had increased consumption of total energy and SFA. Future studies using larger sample sizes are required to confirm significant interaction between SNP rs7903146 and diet on factors that may contribute to MetS in the Saudi population.